Atmospheric N2O product from Svartberget (35.0 m), 2025-03-27–2026-03-31 - Eric Larmanou; Per Marklund (Integrated Carbon Observation System, 2026)
Atmospheric N2O concentrations, both ICOS and non-/pre-ICOS data, delivered by the Atmospheric Thematic Center
Larmanou, E., Marklund, P. (2026). Atmospheric N2O product from Svartberget (35.0 m), 2025-03-27–2026-03-31, European ObsPack, https://hdl.handle.net/11676/lSrBrql3FI6gB7TW61MMulb1
Keywords: Atmosphere Thematic Centre; N2O; dry air mole fraction; time instant, UTC; time instant, UTC; quality flag; quality flag; number of points; number of points; standard deviation of gas mole fraction; standard deviation of gas mole fraction; N2O (dry air mole fraction); N2O (dry air mole fraction); Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser; Meteorology and Atmospheric Sciences; Meteorologi och atmosfärsvetenskap; Physical Geography; Naturgeografi; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap